Produksi Shrimp River Magz Sebagai Upaya Penguatan Eksistensi Komunitas Skateboarder di Yogyakarta - Dweysa Wahabi Anas; Sumekar Tanjung (Asian Journal of Innovation and Entrepreneurship, 2017)
This article aims to explain the production process of Shrimp River Magz in an effort to strengthen the existence of skateboarder community in Yogyakarta. The lack of media reviewing skateboarding in Indonesia has become one of the causes of skateboarding in Indonesia. The method of project creation is carried out through five stages: creative planning, technical planning and equipment, planning of supporting resources, budget planning, and implementation stage. The author also conducted an interview on the skateboarder community to fill the article rubric in the magazine. Based on the results of magazine production, the authors hope that the skateboarder community in Yogyakarta more exposed. The author can also deepen the ability to do design and editing in a magazine production.Â